Conflict-associated wounds and burns infected with GLASS pathogens in the Eastern Mediterranean Region: A systematic review - Amelia Wild; Clare Shortall; Omar Dewachi; Carine Naim; Alex Green; Sarah Hussain; Aula Abbara (BMC Infectious Diseases)
Abstract Background While the relationship between conflict-associated injuries and antimicrobial resistance is increasingly being elucidated, data concerning civilian casualties is sparse. This systematic review assesses literature focused on Global Antimicrobial Resistance Surveillance System (GLASS) Priority Pathogens causing infections in civilian wounds and burns in conflict-affected countries within the World Health Organisation’s Eastern Mediterranean Region Office (EMRO). Methods A systematic literature review was conducted following Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. Five databases and grey literature were searched, identifying studies published from January 2010 to June 2024. Search terms included “wounds”, “burns,” “antimicrobial resistance”, and the twelve countries of interest. Included studies reported resistance of GLASS pathogens. Two reviewers used Covidence to assess papers for inclusion. Data were extracted into a spreadsheet for analysis. Where quantitative data were available, medians, interquartile ranges and percentages were calculated by pathogen and country. Results 621 records were identified; 19 studies met inclusion criteria. Nine of the papers were from Iraq, three from Libya, three from Lebanon, one each from Yemen and Gaza; two reported on conflict affected refugees in Jordan. A total of 1,942 distinct microbiological isolates were reported, representing all four critical and high priority GLASS pathogen categories. Among the isolates, Staphylococcus aureus was the most prevalent (36.3%). Median resistances identified: Methicillin resistant Staphylococcus aureus (n = 680): 55.6% (IQR:49.65–90.3%); carbapenem resistant Pseudomonas aeruginosa (n = 372): 22.14% (7.43–52.22%); carbapenem resistant Acinetobacter baumannii (n = 366): 60.3% (32.1–85%); carbapenem resistant Klebsiella pneumoniae (n = 75): 12.65% (9.73–34.25%); ceftriaxone resistant Escherichia coli (n = 63): 76% (69–84.65%); ceftriaxone resistant Klebsiella pneumoniae (n = 40): 81.45% (76.73–86.18%). Only three studies had a low risk of bias. Discussion Findings imply high rates of GLASS priority pathogens among wounded civilians in conflict-affected EMRO countries. However, evidence was heterogeneous, low quality and sparse in certain countries, highlighting the necessity of effective surveillance including standardised data collection. Improving primary data will facilitate the production of large, high-quality studies throughout the EMRO, including under-represented countries. Conclusion Laboratory diagnostic capacity building and improved surveillance in conflict-affected settings in the Eastern Mediterranean Region are required to assess the burden of GLASS priority pathogens in vulnerable non-combatant populations.